Variable velocity training in the periodized model - Murray, D. P.; Brown, L. E. (Strength and Conditioning Journal, 2006)
This feature discusses the potential benefits of emphasizing movement velocity rather than load during power training. The performance of high-velocity exercise is suggested as an appropriate component of a periodized resistance training program.